Information System Design of Online Motorcycle and Car Repair Shop Using Dijkstra Method - Vira Oktaviani Wijaya; Benny Daniawan (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2021)
Now more people are using motorized vehicles. In addition, the use of technology is also increasing, people are increasingly experiencing fast-paced services. However, in the midst of busy society and online services, some services still have to be done manually, one of which is register for a motorcycle or car repair shop. There are still many people difficult to find the right, closest, and comfortable with the needs of their vehicle. With the existing problems, a vehicle service ordering system is needed that can serve the community quickly and practically, which can be accessed by many people, especially in Tangerang City. With a vehicle service ordering system for motorcycles or car repairshop, people can easily find a repair shop that is the closest to their location and can order without having to wait in long queues. The design of the system for the closest repair shop locations uses the Dijkstra method. The workings of Dijkstra's Algorithm is to create a path to one optimal node at each step. Dijkstra's algorithm has the property to find the point whose distance from the starting point is the shortest. To find out whether the system has been accepted and has met the requirements, the system is tested using the User Acceptance Test (UAT) method, and from the test results, 85.1% of users are satisfied with the system.